The Influence of Work Conflict and Career Development on Employee Performance at the Koto Parik Gadang Diateh District Office - Hidayat, Taufik; Sovia, Arina; Bismark, O.P.; Dakhyar, Dakhyar (Strata Business Review, 2024)
This study discusses the influence of work conflict career development on employee performance at the Koto Parik Gadang Diateh District Office. The method used is descriptive causative. The sampling technique uses a questionnaire method with a sample of 30 respondents with a saturated sampling technique and who are employees at the KPGD district office. Data analysis uses Multiple Linear Regression Analysis with the SPSS for the Windows 23 computer program. This study aims to (1) determine the description of work conflict, career development, and employee performance at the KPGD district office. (2) To determine the influence of work conflict on employee performance at the KPGD district office. (3) To determine career development on employee performance at the KPGD district office. (4) To determine the influence of work conflict and career development on employee performance at the KPGD district office. The study results show that: (1) Work conflict has an average score of 122.6, and its TCR is 81.73% and is inae excellent category. Career development has an average score of 108.1 and a TCR of 72.07% in the pretty good category. Performance has an average score of 124.3 and a TCR of 82.86% in the excellent category. (2) Work conflict has a significant effect on the performance of KPGD sub-district office employees; the t-count value is 10.02,5, the t-table is 2.048 (t-count>t-table), and the sig count is 0.000<0.05, meaning H0 is rejected.